ДЖУМГАЛЬСКОЕ ЗЕМЛЕТРЯСЕНИЕ 9 АПРЕЛЯ 2011 ГОДА - Камчыбеков М.П.; Егембердиева К.А.; Камчыбеков Ы.П.; Чаримов Т.А. (Научно-исследовательский Институт сейсмологии Национальной академии наук Кыргызской Республики, 2015)
The data on geological and tectonic conditions of the Zhumgal cavity, historical seismicity of its area, and results of the macroseismic investigation of the Zhumgal earthquake epicentral zone are presented in the paper.
Keywords: ЗЕМЛЕТРЯСЕНИЕ; EARTHQUAKE; СЕЙСМИЧНОСТЬ; SEISMICITY; ЭПИЦЕНТРАЛЬНАЯ ЗОНА; EPICENTRAL ZONE; ИНТЕНСИВНОСТЬ ЗЕМЛЕТРЯСЕНИЯ; EARTHQUAKE INTENSITY; 550.343.9:551.24:551.240